2015
DOI: 10.1002/pssa.201532442
|View full text |Cite
|
Sign up to set email alerts
|

Controlled growth of PbI2 nanoplates for rapid preparation of CH3NH3PbI3 in planar perovskite solar cells

Abstract: Absorbers for planar perovskite solar cells are often prepared by two‐step deposition methods, where a thick compact PbI2 layer is deposited followed by conversion to perovskite using CH3NH3I solution. The surface of the precursor layer quickly reacts with the CH3NH3I solution, which hinders further diffusion of CH3NH3I into the layer, consequently leading to significant amounts of residual PbI2 at room temperature. Here, we report a novel concept that employs a porous nanostructured PbI2 layer consisting of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 35 publications
7
64
0
1
Order By: Relevance
“…We noticed that this planar growth behavior is amplified at lower concentrations, perhaps due to the lower rate of nucleation. PbI 2 has a planar stacking structure repeating itself along the c-axis, normal to the substrate [17,44]. These planes intrinsically tend to develop from the side faces, in order to balance the surface interactive forces [5,44].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We noticed that this planar growth behavior is amplified at lower concentrations, perhaps due to the lower rate of nucleation. PbI 2 has a planar stacking structure repeating itself along the c-axis, normal to the substrate [17,44]. These planes intrinsically tend to develop from the side faces, in order to balance the surface interactive forces [5,44].…”
Section: Resultsmentioning
confidence: 99%
“…PbI 2 has a planar stacking structure repeating itself along the c-axis, normal to the substrate [17,44]. These planes intrinsically tend to develop from the side faces, in order to balance the surface interactive forces [5,44]. At low solution concentrations, the nucleation rate is low and the grain fronts are less confined by the neighboring grain borders and, therefore, propagate until the complete depletion of the solute from the diffusion layer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is observed that a minor peak exists at the (004) plane associated with 28.3° angle, which disappears when the film is subjected to the SVPT for 180 s, while the peak associated with the (211) plane still exists, which indicates that the crystal structure is still tetragonal. Merger of the peaks at 28.3° and 28.6° has been attributed to crystal distortion, and therefore, a change in the lattice parameters [39]. Thus, excitation of the perovskite by the vibration results in a slight lattice distortion and a change in the lattice parameters.…”
Section: Appl Sci 2018 8 308mentioning
confidence: 99%